Empreendedorismo social e trajetória individual – a história do Banco Liberdade - Oliveira, Rebeca Pires; Maria Elizabeth Antunes Lima, (NAU Social, 2021)
The article presents the relationship between the creator's personal trajectory and the conception of a social entrepreneurship project, proposing a reflection on this type of project as a search for solutions to emerging problems. The focus of the research was Banco Liberdade, located in the city of Belo Horizonte / MG and which offers microcredit. He was inspired by the social business concept of Muhammad Yunus, founder of Gramem Bank, the first social microcredit bank, created in 1970 in Bangladesh, to solve an emerging problem in his country. The methodological approach adopted consisted of rescuing the personal and professional trajectory of the project creator through in-depth interviews and the observation technique. The results highlight a real possibility of undertaking socially and building an innovative business model, producing new ways of thinking and dealing with available resources, in addition to proposing a different management model. It is noticed that the choice of an entrepreneur for certain social situations can reflect their personal experiences that serve as an impulse to seek answers and transform realities that seem unfair and undesirable.